2020
DOI: 10.1039/c9ra08929b
|View full text |Cite
|
Sign up to set email alerts
|

On water catalyst-free synthesis of benzo[d]imidazo[2,1-b] thiazoles and novel N-alkylated 2-aminobenzo[d]oxazoles under microwave irradiation

Abstract: A highly efficient unprecedented catalyst-free microwave-assisted procedure for synthesizing benzo[d]imidazo[2,1-b]thiazoles and N-alkylated 2-aminobenzo[d]oxazol in green media was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The substituent in the imidazole ring is of principal importance for antiviral activity because it was shown that the replacement of the aryl group by a smaller thiophene substituent drastically increases the antiviral action. Catalyst-free MW-assisted method for preparation of annulated heterocyclic structures in aqueous medium was demonstrated by the synthesis of benzo[d]imidazo[2,1-b]thiazoles 44a-l (Scheme 36) [65]. As a polar protic "green" co-solvent capable of easy absorbing MW-radiation, isopropanol was used.…”
Section: Scheme 33 Three-component Synthesis Of Quinazoline Derivatives Of 2-aminobenzothiazole 41a-fmentioning
confidence: 99%
See 2 more Smart Citations
“…The substituent in the imidazole ring is of principal importance for antiviral activity because it was shown that the replacement of the aryl group by a smaller thiophene substituent drastically increases the antiviral action. Catalyst-free MW-assisted method for preparation of annulated heterocyclic structures in aqueous medium was demonstrated by the synthesis of benzo[d]imidazo[2,1-b]thiazoles 44a-l (Scheme 36) [65]. As a polar protic "green" co-solvent capable of easy absorbing MW-radiation, isopropanol was used.…”
Section: Scheme 33 Three-component Synthesis Of Quinazoline Derivatives Of 2-aminobenzothiazole 41a-fmentioning
confidence: 99%
“…The highest antitumor effect was observed for compounds having electron-donor 6-substituents in the benzothiazole fragment and electron-acceptor substituents in the aniline phenyl ring. Catalyst-free MW-assisted method for preparation of annulated heterocyclic structures in aqueous medium was demonstrated by the synthesis of benzo[d]imidazo[2,1-b]thiazoles 44a-l (Scheme 36) [65]. As a polar protic "green" co-solvent capable of easy absorbing MWradiation, isopropanol was used.…”
Section: -Hydrazinobenzothiazoles As Analogs Of 2-aminobenzothiazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that they take into account both the diversity and convolution in organic synthesis, one-pot multi-component reactions are becoming more popular. Perks of the MCR include cost-effectiveness, ease of the process, a low E -factor, good atom economy, and complex product formation with a limited number of synthesis steps. , Also, one-pot synthesis and usage of environmentally benign reaction media are highly desired as they conserve time, limit chemical waste generation, and make practical aspects simpler like purification. , Several MCRs have previously been investigated by our research group. …”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the combined application of microwave-assisted irradiation in green solvents has increased considerably owing to the generation of quick products in the nontoxic environment. In this respect, isopropanol is a very attractive nontoxic green polar solvent for several competent organic reactions that could solubilize numerous reactants at room or high temperatures. Herein, we developed an expedient microwave-assisted simple protocol of 5-substituted oxazoles and diastereoselective 4,5-disubstituted oxazolines derivatives using K 3 PO 4 as a base in an IPA reaction medium …”
Section: Introductionmentioning
confidence: 99%